2017
DOI: 10.1080/14740338.2018.1400008
|View full text |Cite
|
Sign up to set email alerts
|

First experiences with a tool to measure the level of clinical information present in adverse drug reaction reports

Abstract: This is the first tool to give insight in the level of relevant clinical information present in ADR reports. It can be used internationally to compare reports coming from different reporting methods and different types of reporters in pharmacovigilance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Reviewers found that the tool was more difficult to use when multiple suspect products and relevant events were reported. This finding is consistent with the experience of other pharmacovigilance experts . More than one event was reported in 85% of cases, and more than one suspect product was reported in 8% of cases.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Reviewers found that the tool was more difficult to use when multiple suspect products and relevant events were reported. This finding is consistent with the experience of other pharmacovigilance experts . More than one event was reported in 85% of cases, and more than one suspect product was reported in 8% of cases.…”
Section: Discussionsupporting
confidence: 90%
“…Because the provision of data in a structured data field does not necessarily translate to sufficiently complete information from a pharmacovigilance perspective, we conducted a manual review of a subset consumer reports to further assess quality differences between form types (GVR vs ConVR). We used the clinical documentation tool (ClinDoc) to compare the level of reporting of clinical information between the groups of reports . The tool assesses four domains: (1) adverse drug reaction (ADR) description; (2) chronology of the ADR; (3) suspect product description; and (4) patient characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study also found these app reports to be of a high average quality as measured by the vigiGrade completeness score, [ 12 ] with an average of 0.8 (range 0–1). For a report to be of most use for signal detection purposes, it needs to contain high-quality clinical information [ 13 ], which is needed for a good causality assessment. However, little is known concerning the characteristics, quality and the contribution to signal detection of spontaneous ADR reports submitted via an app compared with conventional routes.…”
Section: Introductionmentioning
confidence: 99%